Simulating synergistic impacts of climate change and human induced stressors on a northern Gulf of Mexico estuarine food web - Allen, Kira L.; Garwood, Jason A.; Hu, Kelin; Meselhe, Ehab A.; Lewis, Kristy A. (Frontiers in Marine Science, 2023)
Apalachicola Bay, an estuary located in northwest Florida, is likely to experience a continuing increase in the severity of the effects of changing climate and human-induced stressors, such as sea level rise and changes in freshwater inflow. A coupled hydrodynamic and food web modeling approach was used to simulate future scenarios of freshwater input and sea level rise in Apalachicola Bay from 2020 to 2049 to demonstrate the range of temporal and spatial changes in water temperature, salinity, fisheries species biomasses, total food web biomass and upper trophic level diversity. Additionally, a survey of Apalachicola Bay stakeholders was conducted concurrently with model development to assess stakeholder knowledge and concerns regarding species and environmental changes within the system. Results of the model simulations indicated an increase in water temperature across all scenarios and an increase or decrease in salinity with scenarios of low or high river flow, respectively. These results aligned with the impacts anticipated by stakeholders. White shrimp biomass increased with low river flow and decreased with high river flow, while Gulf flounder biomass decreased across all scenarios. The simulated trends in white shrimp biomass contrasted with stakeholder perceptions. The food web model results also showed an increase in total food web biomass and decrease in upper trophic level diversity across all future scenarios. For all modeled simulations, the largest differences in future environmental variables and species biomasses were between scenarios of low and high river flow, rather than low and high sea level rise, indicating a stronger influence of river flow on the abiotic and biotic characteristics of the estuary. Stakeholders anticipated a future reduction in river flow and increase in sea level rise as negatively impacting the Franklin County economy and stakeholders’ personal interaction with the Apalachicola Bay ecosystem. The use of the ensemble modeling approach combined with the stakeholder survey highlights the use of multiple knowledge types to better understand abiotic and biotic changes in the estuarine system. Results provide insight on the synergistic effects of climate change and human-induced stressors on both the estuarine food web and human community of Apalachicola Bay.